The association of families' socioeconomic and demographic characteristics with parents' perceived barriers to returning to youth sport following the COVID-19 pandemic. (March 2023) - Fleming, Daniel J.M.; Dorsch, Travis E.; Serang, Sarfaraz; Hardiman, Amand L.; Blazo, Jordan A.; Farrey, Tom; Lerner, Jennifer Brown; Solomon, Jon
Abstract: Developmentally appropriate sport contexts have the potential to positively influence young people's physiological, psychological, and social outcomes. However, little is known about how families returned to sport in the wake of COVID-19-related restrictions or how socioeconomic and demographic factors influenced parents' perceptions of barriers to returning. A nationally representative sample ( N  = 6183) of American youth sport parents completed a questionnaire in which they provided demographic information and answered questions related to the barriers they perceived in returning to sport, such as the risk of their child getting sick. Structural equation modeling was used to examine the relationships among a range of socioeconomic and demographic factors and these barriers to returning. Results suggest that parents from racially minoritized and urban neighborhoods held higher levels of concern over health-related and practical barriers to returning to sport. Findings highlight the importance of designing available, equitable, and appropriate youth sport contexts. Highlights: Individuals that reside in urban neighborhoods had higher levels of concern related to health barriers when considering returning to participation. Individuals that identify with a minority racial group report higher levels of health related barriers to their children returning to sport. Those that reside in urban neighborhoods and identify with a minoritized group were more likely to report higher perceptions of practical barriers.